Makna Hidup Wanita Tunasusila yang Berkeluarga: Anita Nur Fadhilah Halid, Ahmad Razak, Perdana Kusuma - Nur Fadhilah Halid, Anita; Razak, Ahmad; Kusuma, Perdana (Fakultas Psikologi Universitas Bhayangkara Jakarta Raya, 2023)
Women who take on multiple roles must consider the risks of the work to be undertaken. In addition, in family life, family members must be open and respectful of each other to avoid conflicts and maintain the integrity of the family itself. However, there are some women who take on multiple roles instead take jobs that deviate from social norms and do not open or respect each other between family members. This study aims to determine the life picture of prostitute women who have families and the meaning of life of prostitute women who have families. The method used in this study is a qualitative research method with a phenomenological approach. Data was collected through interviews and documentation of respondents as many as two people who worked as prostitute women and had families. The results showed that the two respondents had a picture of life that was not much different in terms of economy, relationships and family problems. In addition, the results of the study also showed that both respondents have a meaning of life, but each respondent has a different meaning of life. The implications of this research for prostitute women are as a material for contemplation and as educational material in managing self-concept and family well.